Admissions for antibiotic‐resistant infections in cancer patients during first year of cancer diagnosis: a cross‐sectional study. Issue 11 (5th November 2017) - Slavova‐Azmanova, Neli; Haddow, Livia; Hohnen, Harry; Coombs, Geoffrey; Robinson, James O.; Ives, Angela
Abstract: In this study, linked Western Australian health data were used to determine presence of an antibiotic‐resistant infection (ABRI) for all people diagnosed with a primary invasive cancer in 2009. Of 10 858 cancer cases, 154 (1.42%) had an ABRI. Patients with an ABRI were older (71.5 vs 66 years), and more had died in the year following diagnosis (37.7 vs 20.2%, P < 0.001). The ABRI cohort had a higher proportion of colorectal, genitourinary and haematological cancers (19.5 vs 11.9%; 14.3 vs 9.7% and 16.9 vs 5.8%, respectively). Hospital admissions with an ABRI were longer (22.3 vs 2.9 days, P < 0.001) and had a higher proportion of unplanned admissions (60.3 vs 15.2%), admissions through emergency department (36.8 vs 8.3%) and intensive care admissions (14.9 vs 1.7%, P < 0.001). Patients with solid tumours who developed an ABRI were more likely to have received chemotherapy (35.9 vs 27.8%, P = 0.04). In haematological cancer patients, a greater proportion of the admissions with an ABRI occurred after radiation therapy or chemotherapy ( P = 0.01 and P = 0.005, respectively). This study is the first to report population‐level data on ABRI in cancer patients. Patients with an ABRI had more hospital admissions and poorer outcomes.